Conflict of interest among Italian medical oncologists: a national survey. Issue 6 (30th June 2018) - DeCensi, Andrea; Numico, Gianmauro; Ballatori, Enzo; Artioli, Fabrizio; Clerico, Mario; Fioretto, Luisa; Livellara, Virginia; Ruggeri, Benedetta; Tomirotti, Maurizio; Verusio, Claudio; Roila, Fausto
Abstract : Objectives: To assess Italian medical oncologists' opinion on the implications of conflict of interest (COI) on medical education, care and research, and to evaluate their direct financial relationships. Design: National cross-sectional survey conducted between March and April 2017 among Italian oncologists. Setting: Online survey sponsored by the Italian College of Medical Oncology Chiefs through its website. Participants: Italian oncologists who filled out an anonymous questionnaire including 19 items and individual and working characteristics. Main outcome measure: The proportion of medical oncologists perceiving COI as an outstanding issue and those receiving direct payments from industry. Results: There were 321 respondents, representing 13% of Italian tenured medical oncologists. Overall, 62% declared direct payments from the pharmaceutical industry in the last 3 years. Sixty-eight per cent felt the majority of Italian oncologists have a COI with industry, but 59% suppose this is not greater than that of other specialties. Eighty-two per cent consider that most oncology education is supported by industry. More than 75% believe that current allocation of industry budget on marketing and promotion rather than research and development is unfair, but 75% consider it appropriate to receive travel and lodging hospitality from industry. A median net profit margin of €5000 per patient enrolled in an industry trial was considered appropriate for the employee institution. Sixty per cent agree to receive a personal fee for patients enrolled in industry trials, but 79% state this should be reported in the informed consent. Over 90% believe that scientific societies should publish a financial report of industry support. Finally, 79% disagree to being a coauthor of an article written by a medical writer when no substantial scientific contribution is made. Conclusions: Among Italian oncologists COI is perceived as an important issue influencing costs, education, care and science. A more rigorous policy on COI should be implemented.